Transforming Community Welfare with Cash Waqf Education: A Case Study of Riak Siabun Village in Seluma District - Friyanti, Yunida Een; Syaifuddin; Pramadeka, Katra; Hartini, Kustin; Afrianty, Noni (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2024)
This study aims to determine the literacy of the community before and after the implementation of education on the optimization of cash waqf management so that it can encourage the welfare of the people of Riak Siabun I Village, Seluma Regency about the optimization of cash waqf. The method used is the Community Based Research (CBR) approach. The sample of this research amounted to 100 people. The results of this study indicate that the understanding of cash waqf in increasing interest in waqf based on the pretest results is still diverse. In addition, only some of them understood about cash waqf but not so far understood and only some of them were interested in waqf money. However, the posttest results showed a significant increase in the participants' understanding based on the results of the post-test, 100% already knew clearly about cash waqf. Efforts to increase the understanding of Riak Siabun I Village, Seluma Regency regarding cash waqf were successful.